Perception of Peruvian Students Studying in Biological Sciences about the Advantages of Virtual Classes during the COVID-19 Pandemic - Aldo Bazán-Ramírez; Walter Capa-Luque; Homero Ango-Aguilar; Roberta Anaya-González; Víctor Cárdenas-López (MDPI AG, 2023)
There is significant educational research interest regarding the assessment of the benefits of virtual education implemented during the COVID-19 pandemic for university programs that were essentially face-to-face. The objective of the study was to determine the effect of the management of online resources that the teacher had on the valuation of the advantages of online classes in biological sciences, mediated by the students' perception of virtual practices as well as the accessibility and use of online resources. A total of 332 Peruvian students studying in biological sciences from a public university, enrolled in five undergraduate academic years, of which 184 were women and 148 were men, participated. A non-experimental predictive design of causal relationships was used with the methodology of structural equation modeling. According to the SEM model (CFI and TLI > 0.95, RMSEA and SRMR < 0.05), the valuation of the advantages of virtual classes during the pandemic was significantly predicted by the valuation of virtual practices (positively) as well as by the accessibility and management of online resources by students (negatively); likewise, the use and mastery of digital and online resources by teachers had an indirect effect on the valuation of virtual classes, but direct effects on virtual practices and accessibility to digital resources by students. Also, virtual practice was the most crucial variable in predicting the valuation of online classes (β = 0.48, p < 0.001). In conclusion, the student's perception of the teachers' handling of online resources during the COVID-19 pandemic was determinant as a favorable valuation of the advantages offered by online classes, a relationship that is mediated by virtual practices and accessibility to online resources.